Pembinaan usaha pengolahan dan pemasaran produksi kijing di Desa Sungai Paku Kecamatan Kampar Kiri, Kampar - Bustari Hasan; Dian Iriani; N Ira Sari; Trisla Warningsih; Fitra Suzanti; Evrin Septyanti (Unri Conference Series: Community Engagement, 2019)
One of the fishery products in Sungai Paku village is kijing, which is a freshwater mussel that lives naturally at the bottom of the river, and a community fish pond that utilizes leftovers from aquaculture. The potential of kijing is quite large and has good nutritional value especially the content of essential amino acids and Omega 3 fatty acids (EPA and DHA), but have not been utilized optimally. The objectives of this activity were to 1. Increase the knowledge and skills of the community to become creative, productive and independent processors, 2. Provide knowledge about the management of product licenses from BPOM (P-IRT), and 3. Provide production management skills and marketing strategies so that production develops and continuous (sustainable). The methods used in the implementation of this activity were: lectures, discussions, and direct practice of making crackers and snack products of kijing with various flavours: cheese, barbecue, and spicy flavor, with a farmer group Alam Bendungan consists 10 people who have been selected. From the implementation of this activity the service program target has been achieved well (100%), in which the Paku River village community which is incorporated into farmer group the Alam Bendungan Sungai Paku Village has become a creative, productive and independent processor, has knowledge of managing product licenses from BPOM (P-IRT), skilled in product management and marketing strategies so that production develops and continues (sustainable).